Aspergillus flavus and Fusarium verticillioides Interaction: Modeling the Impact on Mycotoxin Production - Camardo Leggieri, Marco; Giorni, Paola; Pietri, Amedeo; Battilani, Paola (Frontiers in Microbiology, 2019)
The influence of climate change on agricultural systems has been generally accepted as having a considerable impact on food security and safety. It is believed that the occurrence of mycotoxins will be greatly affected by future climate scenarios and this has been confirmed by recent data. Temperature (T) and CO2 increases, variation in rain intensity and distribution, as well as extreme weather events, affect the dominant fungal species in different ways, depending on their ecological needs. Therefore, the aim of this work was to study Aspergillus flavus (Af) and Fusarium verticillioides (Fv) co-occurrence in vitro in order to collect quantitative data on the effect of fungal interaction on growth and mycotoxin production and develop functions for their description. Experimental trials were organised with the cited fungi grown alone or together. They were incubated at different T regimes (10-40°C, step 5°C) for 21 days. Fungal growth was measured weekly, while AFs and FBs were quantified at the end of the incubation period. Temperature and incubation time significantly affected fungal growth both for Af and Fv (p≤0.01), and a significant interaction between T and the presence of one versus both fungi influenced the amount of AFs and FBs produced. Each fungus was affected by the presence of the other fungus; in particular, Af and Fv showed a decrease in colony diameter of 10% and 44% respectively, when they were grown together, compared to alone. The same influence was not found for mycotoxin production. In fact, the dynamic of toxin production in different temperature regimes followed a comparable trend with fungi grown alone or together, but a significant impact of inoculum × temperature interaction was highlighted. Fungal growth and toxin production in different T regimes were well described, both for AFs and FBs, by a Bete function. These results are the first attempt to model mycotoxigenic fungal co-occurrence under several T regimes; this is essential in order to improve effective prediction of growth and mycotoxin production by such fungi.